ANALISIS PERBANDINGAN PREDIKSI KEBANGKRUTAN PERUSAHAAN DENGAN MENGGUNAKAN MULTIVARIATE DISCRIMINANT ANALYSIS DAN REGRESI LOGISTIK PADA PERUSAHAAN PERTAMBANGAN BATUBARA PERIODE 2010-2014 - Asnita, Rozza; Fuadi, Raida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This research objective is to predict the bankruptcy in sector property and real estate which listed in Indonesia stock exchange: using discriminant analysis and logistic regression period 2010-2014. Sampling methods used in the research was purposive sampling. The hypothesis examination is tested by discriminant analysis and logistic regression analysis to determine significant differences in financial ratios such as current ratio, leverage ratio, net profit margin, debt to equity, operating profit margin, total asset turnover to distinguish a group of companies that are considered insolvent and not statistically bankrupt on listed companies in Indonesia stock exchanges in coal mining sector during the period of 2010-2014. The data source of this research come from Indonesia Stock Exchange (IDX).The result of this research showed that the accuracy of the models using Discriminant analysis was 80.4% and Logistic Regression Analysis was 88.2%. In the discriminant analysis showed that the significant variables were leverage ratio and net profit margin. As for the second logistic regression showed that significant variables were leverage ratio, net profit margin, and total assets turnover that could affect the company's bankruptcy prediction coal mining sector in the period 2010 to 2014.Keywords bankruptcy, current ratio, leverage ratio, net profit margin, debt to equity, operating profit margin, total asset turnover, logistic regression. discriminant analysis.